2002
DOI: 10.2320/matertrans.43.2943
|View full text |Cite
|
Sign up to set email alerts
|

Implant Applications of Highly Corrosion-Resistant Ti-15Zr-4Nb-4Ta Alloy

Abstract: The release of metal ions from the Ti-15Zr-4Nb-4Ta alloy in pseudo body fluids was compared with those from Ti-6Al-4V and vanadium-free Ti-6Al-7Nb alloys widely used as implantable titanium alloys throughout the world, in order to choose an optimum acceleration solution for immersion testing. Bone plates, artificial hip joints of the cementless type and artificial tooth implants were experimentally fabricated using the Ti-15Zr-4Nb-4Ta alloy. The quantities of titanium ions released from the titanium alloys int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Metastable titanium alloys are interesting in deformation properties, such as extraordinary elasticity, 1,2) various deformation mode, [3][4][5] shape memory effect 6) and marvelous clayey plasticity; 7) therefore they are now recognized as advanced materials for biomedical applications, 8,9) etc. These properties are concerned with the inherent transformations including 0 -, 00 -martensites and !-phase athermally formed by quench of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Metastable titanium alloys are interesting in deformation properties, such as extraordinary elasticity, 1,2) various deformation mode, [3][4][5] shape memory effect 6) and marvelous clayey plasticity; 7) therefore they are now recognized as advanced materials for biomedical applications, 8,9) etc. These properties are concerned with the inherent transformations including 0 -, 00 -martensites and !-phase athermally formed by quench of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…• Ti-15Zr-4Nb-4Ta 26 are being investigated, in addition to dental casting of Ti-15Zr-4Nb-4Ta 27 and the beta-type titanium alloys listed previously. The usage of Ti6Al-7Nb 28 is increasing over Ti-6Al-4V.…”
Section: Activity Of Jim Metallic Biomaterials and Healthcare Materiamentioning
confidence: 99%
“…1) Our research group previously reported on the effects of Zr, Nb, Ta and Pd on the mechanical properties of Ti alloys and the biocompatibilities of these alloys with cultured cells, and on the corrosion resistance of Ti alloys, as determined using anodic polarization tests in synthetic body fluids. [2][3][4][5][6][7][8][9][10][11][12][13][14] The mechanical strength at room temperature of this new Ti-Zr-Nb-Ta alloy annealed at 700 C for 2 h is increased by adding Zr and small quantities of oxygen and nitrogen. 4,5,9) The anodic polarization property of the Ti alloy is improved when Zr, Nb, Ta and Pd are added, because the resultant ZrO 2 , Nb 2 O 5 , Ta 2 O 5 and PdO strengthen the TiO 2 passive film formed on the Ti alloy.…”
Section: Introductionmentioning
confidence: 99%